Gobbling activity of eastern wild turkeys relative to male movements and female nesting phenology in South Carolina - Michael J. Chamberlain; Patrick H. Wightman; Bradley S. Cohen; Bret A. Collier (Wildlife Society Bulletin)
ABSTRACT Wild turkeys (Meleagris gallopavo) use a polygynous mating system, and males must balance fitness benefits of courtship displays against costs of their reproductive strategies. Wild turkeys are the only gamebird species in the contiguous United States hunted primarily during their reproductive period. Managers attempt to implement seasons that allow for hunter satisfaction while limiting effects to reproduction and ensuring sustainable populations. To minimize illegal harvest, managers often attempt to set spring hunting seasons when gobbling activity is high and females are actively incubating nests. Gobbling activity varies significantly both temporally and spatially, and relationships between gobbling activity and reproductive phenology are unclear. We used autonomous recording units and Global Positioning System transmitters to monitor gobbling activity by male eastern wild turkeys (M. g. silvestris) and evaluate fine‐scale movements of male wild turkeys and nesting chronology of females on the Webb Wildlife Management Area Complex in South Carolina, USA, during 2015–2016. Based on 19,126 gobbles and movement ecology data from 99 wild turkeys (70 F, 29 M), we found no discernable pattern to support the hypothesis that gobbling activity increases with onset of incubation by females. We also observed no definable relationship between daily movements of males and gobbling activity, likely driven by the considerable daily variability in gobbling activity. We noted apparent lags in gobbling activity relative to nest initiation (onset of laying), and offer that understanding mechanisms underlying these apparent lags may be important to improving our understanding of reproductive ecology in wild turkeys. Research evaluating confounding influences of hunting activity and male mortality during the breeding season on gobbling activity and wild turkey population dynamics is warranted. © 2018 The Wildlife Society.